Analysis of Patient Experience Dimensions and Their Implications in Improving Customer Engagement and Customer Delight at Hospital X - Selvyana C. Palit; Ratna Indrawati (Dinasti Health and Pharmacy Science, 2026)
Medical institutions currently face the challenge of going beyond conventional satisfaction standards to create customer delight through strategic patient experience management. This study aims to analyze the dimensions of patient experience and their implications for increasing customer engagement and delight among internal medicine patients at Hospital X. This quantitative study used a cross-sectional design involving 99 respondents selected through a purposive sampling method. Data analysis was conducted using the Three Box Method for descriptive review and Path Analysis to examine the structural relationships between variables. The results of the descriptive analysis indicate that patient experience is in the high category (77.47), with the Information and Education dimension as the main contributor to excellence (78.75). In contrast, the Continuity and Transition dimension was identified as a relative weak point (75.38), especially in the aspect of drug side effect education. The findings of the path analysis confirmed that patient experience has a direct significant effect on customer engagement and customer delight. Customer engagement is proven to act as a mediating variable that strengthens the transmission of the influence of patient experience in creating deep emotional satisfaction. This research model has a predictive power of 66.3% of the variance in customer delight. This study concludes that optimizing every point of interaction and strengthening patient emotional engagement is a fundamental instrument for hospital management to build long-term loyalty and competitive advantage.